Measures Taken to Improve Safety in Russian Coal Mines - Rostislav Magomet, Vladimir Soloviov, Jozef Parchanski (International Journal of Advanced Science and Technology, 2020)
In assessing the current state and prospects for the development of coal mining in Russia, a number of objective factors need to be considered. These include the following: economic performance of the industry under consideration and its fluctuations prompted by market conditions both in Russia and beyond; industrial safety and labor protection performance; indicators for efficiency and effectiveness of the reconstruction of the coal mining industry. As of now, coal mining is a major industry in Russianeconomy. As world prices for coal dropped starting in 2011, a rising trend of coal consumption in the world gave way to a decline in international trade in coal. A drop in fatal injuries in coalmines per 1,000 employees reflects the current state of industrial safety and labor protection in the sector; the risk of accidents, however, remains high. The reason for most accidents that have actually taken place were explosions of methane, hence an urgent need in improving the quality of professional training of employees working underground, in funding preventive measures and staff training to ensure greater mine safety and, finally, in acquiring safety equipment. Safety measures concern, above all, the rules relating to pulverized coal and gas, as well as better conditions of early degassing of coal deposits and ventilation of mines.Keywords: Russian coal mining industry, coal mining, safety in coal mining, coalbed degassing, prospects for the development of the coal mining industry, personnel, industrial efficiency, development principles, methane gas disposal